2018
DOI: 10.1016/j.jtcvs.2017.09.131
|View full text |Cite
|
Sign up to set email alerts
|

Midterm outcomes after postoperative delirium on cognition and mood in patients after cardiac surgery

Abstract: Postoperative delirium is associated with increased anxiety and depression at 6 to 9 months postcardiac surgery. Future investigation should seek to evaluate the utility of screening programs for affective disorders in those individuals who develop delirium in the postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 33 publications
1
19
1
1
Order By: Relevance
“…Many of previous studies [28,37] agree with our findings that postoperative verbal memory decline was correlated with length of bypass time. In contrast to our study, Nguyen et al [31] observed no differences in cognitive functions between the delirious and non-delirious subjects after 6 to 9 months. This dissimilarity in the reported severity and type of cognitive dysfunction between different studies may be attributed to the difference in: methodology, study population characteristics, the selected definition of cognitive impairment, and the time of postoperative evaluation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Many of previous studies [28,37] agree with our findings that postoperative verbal memory decline was correlated with length of bypass time. In contrast to our study, Nguyen et al [31] observed no differences in cognitive functions between the delirious and non-delirious subjects after 6 to 9 months. This dissimilarity in the reported severity and type of cognitive dysfunction between different studies may be attributed to the difference in: methodology, study population characteristics, the selected definition of cognitive impairment, and the time of postoperative evaluation.…”
Section: Discussioncontrasting
confidence: 99%
“…As regards predictors affecting cognitive functions, this research found no significant differences in cognitive performance between male and female patients and also between smokers and non-smokers. These results were in the same line with many of previous studies [26,31,32]. In our work, we found no role for ICU-LOS on cognition as documented also by Harrington et al [33].…”
Section: Discussionsupporting
confidence: 94%
“…При тяжелых соматических заболеваниях нередко развиваются различные психические расстройства: астенические, неврозоподобные состояния, депрессии, психозы. Существует большое количество клинических исследований частоты соматогенного делирия в послеоперационном периоде, при инсульте, а также в остром периоде ИМ [7][8][9][10][11][12]. Среди больных ИБС в 2 раза чаще, чем в общей популяции, встречаются депрессивные расстройства, наличие которых негативно влияет на прогноз [13].…”
Section: оригинальные статьи § введениеunclassified
“…Cognitive functions were reported to be mildly or not significantly impaired after transcatheter aortic valve implantation (TAVI) [115]. Postoperative delirium is associated with increased anxiety and depression at 6 to 9 months, and future investigation should seek to evaluate the utility of screening programs for affective disorders in those individuals who develop delirium in the postoperative period [116].…”
Section: Reviewmentioning
confidence: 99%